Eksistensi Mimbar Masjid Bersejarah Jakarta - Ahmad Irfan; Nurbaiti Bahrudin; Nicky Rosadi (FOCUS, 2022)
The pulpit which existed at the time of the Prophet, then it became a sunnah that was respected, so that in generations after the Prophet the existence of the pulpit was still maintained. This study attempts to describe the existence of the pulpit at a historic mosque in Jakarta. This research uses a qualitative research approach with analytical descriptive method. The research location takes place in historic mosques in Jakarta. Data collection techniques using interviews, observation, documentation. The results of this study indicate that historic Jakarta mosques still use pulpits with various models so that their existence is still maintained today.